PERANCANGAN INSTAGRAM GUIDEBOOK DAN KONTEN PROMOSI BRAND INFINITE APPAREL UNTUK MENJANGKAU TARGET PASAR USIA 17-30 TAHUN DI KOTA MALANG - Kurniawan, Michael Nathanael; Pratama, Bintang Pramudya Putra; Nugroho, Didit Prasetyo (Ma Chung Press, Universitas Ma Chung, 2025)
The rapid growth of social media usage, especially Instagram, has created significant opportunities for local brands to strengthen their identity and expand their market reach. Infinite Apparel, a local clothing brand from Malang with a modern spiritual concept, has yet to develop a directed visual communication strategy, resulting in low brand awareness among the target audience aged 17-30 in Malang City. This study aims to design an Instagram Guidebook and promotional visual content as a strategic solution to build brand identity and enhance audience engagement. The design process follows the Design Thinking framework, which consists of five phases: empathize, define, ideate, prototype, and test. Data collection was carried out using a mixed-method approach (qualitative and quantitative) through interviews with the brand owner, competitor content observation, literature review, and questionnaire distribution to the target audience in Malang. The main outcomes of the design include a comprehensive Instagram Guidebook containing visual and communication style guidelines, as well as promotional content designs for formats like feed, reels, and stories. Additionally, supporting media such as product mockups were also designed. Implementation test results of the guide showed that 80% of the content produced by designers complied with the established visual standards, proving the guidebook's effectiveness in maintaining consistency and strengthening the brand's visual identity on the digital platform.